Aspek Biologi Waanders's hard-lipped barb (Osteochilus waandersii) di Sungai Tambatan, Sumatera Utara, Indonesia - Siti Jurniah Nasution; Rivo Hasper Dimenta (BIOEDUSCIENCE, 2021)
Background: Waanders’s hard-lipped barbs or scientifically known as Osteochilus waandersii belong to the family Cyprinidae with the potamodromous category. This fish can be found in the Tambatan river. It has the potential for commercial consumption or ornamental fish. Methods: This study was conducted in the Tambatan river from November to January 2021. The determination of three research stations was carried out using a purposive sampling method. Sampling was undertaken using cast nets. Furthermore, data analyzed were growth patterns, condition factors, and gonad maturity levels. Results: The growth patterns of male (1.944) and female (2.379) Osteochilus waandersii were in a negative allometric category. Besides, The Fulton's condition factor for male fish ranged from 0.42 - 3.43 with an average of 1.05, while that for female fish ranged from 0.59 - 3.67 with an average of 1.47. The result of the observation on the gonad maturity level for male and female O. waandersii in the Tambatan river indicated that they were dominated by fish with gonad maturity stage I (immature). Conclusions: Waanders’s hard-lipped barbs O. waandersii found were in the stage towards the mature level.